2019
DOI: 10.3847/2041-8213/ab01e1
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Variability of O and B Stars Revealed from 2-minute Cadence Light Curves in Sectors 1 and 2 of the TESS Mission: Selection of an Asteroseismic Sample

Abstract: Uncertainties in stellar structure and evolution theory are largest for stars undergoing core convection on the main sequence. A powerful way to calibrate the free parameters used in the theory of stellar interiors is asteroseismology, which provides direct measurements of angular momentum and element transport. We report the detection and classification of new variable O and B stars using high-precision short-cadence (2-min) photometric observations assembled by the Transiting Exoplanet Survey Satellite (TESS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 47 publications
6
83
1
Order By: Relevance
“…Nonetheless, our addition of K2 high frequency pulsators to the total number of upper main sequence variable stars, and the large amplification soon by TESS, is bound to add incrementally to the much needed calibration of stellar evolution theory of hot massive stars. With TESS, massive star asteroseismology will certainly be getting a boost (Pedersen et al 2019b;Bowman et al 2019a). Figure 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, our addition of K2 high frequency pulsators to the total number of upper main sequence variable stars, and the large amplification soon by TESS, is bound to add incrementally to the much needed calibration of stellar evolution theory of hot massive stars. With TESS, massive star asteroseismology will certainly be getting a boost (Pedersen et al 2019b;Bowman et al 2019a). Figure 11.…”
Section: Resultsmentioning
confidence: 99%
“…CoRoT while successful, only provided a handful of stars for which detailed asteroseismic analyses were possible. On the other hand, K2 (Bowman et al 2019a), and more recently TESS (see Pedersen et al 2019b for diverse variability of OB stars in TESS sectors 1 and 2), have begun to remedy this lack of continuous, long-term, high-precision photometric data for massive stars.…”
Section: Introductionmentioning
confidence: 99%
“…We are just beginning to scratch the surface of the observed pulsating EBs, and the hybrid pulsating nature is still rarely exploited. We also expect to have many B-type β Cephei/SPB hybrid pulsators (Handler et al 2009;Pedersen et al 2019). Hybrid p-and g-mode pulsations have also been found in sub-dwarf B-stars (sdB) (Baran et al 2011(Baran et al , 2017Reed et al 2010Reed et al , 2019 and proto-Helium Extremely Low Mass White Dwarfs (Maxted et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other targets showing this behaviour in the periodogram of their TESS light-curves should be considered as promising magnetic candidates. Such candidates have been identified for OB stars in sectors 1 and 2 by Pedersen et al (2019) and for A stars in sectors 1 to 4 by Sikora et al (submitted). They are prime targets for future spectropolarimetric observations.…”
Section: Discussionmentioning
confidence: 90%
“…Such efforts are led in parallel with similar studies classifying variability types in OBA stars observed by TESS (e.g. Pedersen et al 2019;Balona et al 2019;Sikora et al, submitted; for a complementary study of Ap stars using TESS data see Cunha et al, submitted).…”
Section: The Mobster Collaborationmentioning
confidence: 88%